Modeling and categorizing standardized artifacts for scheduling occupancy on building construction sites - Morin Pépin, Stéphane; Francis, Adel (Frontiers in Built Environment, 2024)
The new trend in planning building projects involves incorporating space management on the construction site. Failing to consider the management of site operations can lead to either relaxed or congested construction sites. This is because labor, tools, equipment, and materials all require space. It is important to plan for the circulation and temporary storage of materials, including recycling, reuse, and disposal. Temporary installations and finished products also take up space and can impact traffic flow. For example, partitions can impair traffic flow, while finished flooring can restrict it. The occupation of spaces also changes as the work progresses, so it is important to monitor and accommodate these changes. Therefore, space management needs to be coordinated throughout the construction phase. Traditional planning methods do not consider the analysis of critical spaces or their evolution over time. As a result, they produce schedules that do not reflect the reality of the construction site. Dynamic space-time planning means modelling the operational flow in different sectors of the construction site to optimize the construction process. Efficient space occupation allows for more effective utilization of available resources. This paper aims to analyze the spatial requirements of various construction operations and develop standardized artifacts that integrate spatial information into the schedule. To achieve this objective, the methodology aims to: (i) Conduct site surveys to collect data and analyze construction operations and their spatial needs; (ii) Define the necessary parameters for determining the occupancy rate (OR); (iii) Develop the needed artifacts for representing the static models based on the survey results and the developed occupancy parameters to visually depict and compute various types of occupancy and operations;(iv) Conduct workshops with the professionals in the construction industry. The participants were asked to provide feedback on whether the artifacts effectively captured the various aspects of construction work, such as equipment, tools, materials, and safety protocols. The aim is to validate that the artifacts as reliable representations of real-life construction scenarios. The feedback and input provided by the professionals helped to ensure that the artifacts were accurate, informative, and valuable for training purposes in the construction industry.